Minimal-invasive explantation of sulcus-fixated toric-multifocal additional intraocular lenses despite excellent visual measurements: A case report - Jens Schrecker; Achim Langenbucher (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2022)
A 40-year-old male patient was referred to our hospital for cataract surgery in both eyes with the explicit wish to get simultaneously rid of his eyeglasses. To allow for postoperative flexibility, we performed a bilateral implantation of a monofocal intraocular 'standard' lens in combination with an additional toric-multifocal lens. During the postoperative examinations the patient complained about pronounced halos in twilight and darkness. Visual acuity was excellent for distance, intermediate and near distances. Both IOLs were well centered and showed no tilt or other morphological discrepancies. Despite our extensive treatment efforts, including supportive training for neural adaptation, the patient perceived no signs of improvement. Finally, we had to explant both additional IOLs. The primary corneal incisions were bluntly reopened and the additional IOLs were removed in a minimal traumatic procedure. With the retained IOL in the capsular bag and subsequently ordained progressive eyeglasses the patient obtained full vision at all distances. Our preoperative planning to compensate for presbyopia with a separate IOL, proved to be a good decision. Otherwise, the explantation of a multifocal IOL, ingrown in the capsular bag, could have entailed a number of complications. In such delicate cases, additional IOL may offer a very save and simple alternative.